BRAND IMAGE, PRODUCT QUALITY, PRICE, DAN INTEREST BUYING PADA MS GLOW - Evieana R Saputri; Hermala Kusumadewi; Rafly Galih Saputra (MANAJEMEN DEWANTARA, 2022)
This study aims to find out that brand image, product quality, and price affect the interest in buying MS Glow products. The method used in this study is a quantitative method using multiple linear regression analysis. The research data was obtained through distributing questionnaires with sampling, the population determination that I used with the random sampling technique used totaled 57 respondents taken from students. The results of this study indicate that brand image and product quality affect interest buying of MS Glow products. Meanwhile, simultaneous testing shows that brand image, product quality and price affect interest buying of MS Glow products.